2014
DOI: 10.1126/scisignal.2005411
|View full text |Cite
|
Sign up to set email alerts
|

Partial inhibition of gp130-Jak-Stat3 signaling prevents Wnt–β-catenin–mediated intestinal tumor growth and regeneration

Abstract: Most colon cancers arise from somatic mutations in the tumor suppressor gene APC (adenomatous polyposis coli), and these mutations cause constitutive activation of the Wnt-to-β-catenin pathway in the intestinal epithelium. Because Wnt-β-catenin signaling is required for homeostasis and regeneration of the adult intestinal epithelium, therapeutic targeting of this pathway is challenging. We found that genetic activation of the cytokine-stimulated pathway mediated by the receptor gp130, the associated Jak (Janus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 66 publications
(110 reference statements)
4
53
1
Order By: Relevance
“…Secondly, in AOM-related tumor models tumors with increased size and proliferation are seen in the presence of epithelial cells with increased STAT3 activation (i.e., cells with a gp130 Y757F mutation that prevents SOCS3 activation or with SOCS3 deficiency) (39). This finding is mirrored in the Apc min/+ tumor model in that Apc min/+ mice with mutated gp130 that cannot bind STAT3 and thus manifest reduced STAT3 activation, exhibit a decreased number and size of tumors as well as reduced early stage tumor formation; reciprocally, Apc min mice with gp130 that cannot bind SOCS3 and thus manifests increased STAT3 signaling, exhibit increased tumor formation (40). Taken together, these data provide more or less definitive evidence that STAT3 activation plays a necessary and sufficient role in the 2 nd Stage of inflammation associated epithelial cell tumor formation.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Secondly, in AOM-related tumor models tumors with increased size and proliferation are seen in the presence of epithelial cells with increased STAT3 activation (i.e., cells with a gp130 Y757F mutation that prevents SOCS3 activation or with SOCS3 deficiency) (39). This finding is mirrored in the Apc min/+ tumor model in that Apc min/+ mice with mutated gp130 that cannot bind STAT3 and thus manifest reduced STAT3 activation, exhibit a decreased number and size of tumors as well as reduced early stage tumor formation; reciprocally, Apc min mice with gp130 that cannot bind SOCS3 and thus manifests increased STAT3 signaling, exhibit increased tumor formation (40). Taken together, these data provide more or less definitive evidence that STAT3 activation plays a necessary and sufficient role in the 2 nd Stage of inflammation associated epithelial cell tumor formation.…”
Section: Introductionmentioning
confidence: 94%
“…Taken together, these data provide more or less definitive evidence that STAT3 activation plays a necessary and sufficient role in the 2 nd Stage of inflammation associated epithelial cell tumor formation. Additional studies showing that Apc min/+ mice with epithelial cell-specific decreased STAT3 activity manifest decreased tumor formation indicate that the STAT3 signaling occurring in epithelial cells is the critical locus of tumor-inducing STAT3 activity (39, 40). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signal transducer and activator of transcription 3 (STAT3) remains inactive in normal cells until activated by various cytokines and growth factors, such as IL-6 and EGF family members. However, STAT3 is often detected to be continuously activated in cancer cells, and several STAT3 knockout mouse models revealed that STAT3 is a critical oncogenic transcription factor for tumorigenesis in skin [21], intestine [22], and liver [23]. A suppressor of cytokine signaling 3 (SOCS3) is involved in a negative feedback mechanism that turns off the activation of STAT3 [24].…”
Section: Introductionmentioning
confidence: 99%